Randomised controlled trial of active case management to link hepatitis C notifications to treatment in Tasmania, Australia: a study protocol - Tim Spelman; David Iser; Margaret Hellard; Joseph Doyle; Louise Owen; Alexander Thompson; Fay H Johnston; Shannon Melody; N Scott; Mark A Stoové; A E Pedrana; Jacqui Richmond; et al. (BMJ Open, 2022)
Introduction By subsidising access to direct acting antivirals (DAAs) for all people living with hepatitis C (HCV) in 2016, Australia is positioned to eliminate HCV as a public health threat. However, uptake of DAAs has declined over recent years and new initiatives are needed to engage people living with HCV in care. Active follow-up of HCV notifications by the health department to the notifying general practitioner (GP) may increase treatment uptake. In this study, we explore the impact of using hepatitis C notifications systems to engage diagnosing GPs and improve patient access to treatment.Methods and analysis This study is a randomised controlled trial comparing enhanced case management of HCV notifications with standard of care. The intervention includes phone calls from a department of health (DoH) specialist HCV nurse to notifying GPs and offering HCV management support. The level of support requested by the GP was graded in complexity: level 1: HCV information only; level 2: follow-up testing advice; level 3: prescription support including linkage to specialist clinicians and level 4: direct patient contact. The study population includes all GPs in Tasmania who notified HCV diagnosis to the DoH between September 2020 and December 2021. The primary outcome is proportion of HCV cases who initiate DAAs after 12 weeks of HCV notification to the health department. Secondary outcomes are proportion of HCV notifications that complete HCV RNA testing, treatment workup and treatment completion. Multiple logistic regression modelling will explore factors associated with the primary and secondary outcomes. The sample size required to detect a significant difference for the primary outcome is 85 GPs in each arm with a two-sided alpha of 0.05% and 80% power.Ethics and dissemination The study was approved by University of Tasmania’s Human Research Ethics Committee (Protocol ID: 18418) on 17 December 2019. Results of the project will be presented in scientific meetings and published in peer-reviewed journals.Trial registration number NCT04510246.Trial progression The study commenced recruitment in September 2020 and end of study expected December 2021.